Influence of Stakeholder Inclusive Initiation on Performance of Infrastructure Public Projects in Tharaka South Sub County - Nicholas, Suleiman; Muiruri , Paul (International Journal of Entrepreneurship and Project Management, 2023)
Purpose: The aim of the study was to explore the influence of stakeholder inclusive initiation on performance of infrastructure public projects in Tharaka south sub county Methodology: The study adopted descriptive research design. The unit of observation included 50 project committee, 75,250 project beneficiaries, 20 government officials, 20 implementing agencies and 65 community leaders. The study used purposive sampling method to obtain 143 respondents from the target population. Questionnaires were used to obtain firsthand information by use of open and closed ended questions for project beneficiaries. The study used both primary and secondary data. The quantitative data was analyzed by the use of inferential analysis and descriptive analysis in reference to statistical package of social sciences. The descriptive analysis helped to generate the percentage, means and frequencies. Tables were applied in data presentation. Findings: Based on the finding stakeholder inclusive initiation play an essential role in performance of infrastructure public project (Î²=0.569, Ï=0.00) From the feedback of most of the participants with a mean of 2.90, were moderate that they get in problem analysis. They also disagreed that they were allowed to give their views covering the feasibility study of the project by a mean of 2.965. The participants moderate that they were engaged in charter development by a mean of 2.923. However, they strongly disagreed that they were engaged in project documentation with a mean of 2.671. Lastly, they disagreed that they were allowed to fully participate at every activity at this stage with a mean of 2.748. Unique Contribution to Theory, Practice and Policy: Stakeholders' theory may be used to anchor future studies on Public Projects. The study recommended that stakeholders get equally involved to every stage and should be a continuous process which create environment of tracking every activity to ensure performance of infrastructure public projects.